Professional Skepticism, Audit Experience, Time Pressure and Fraud Detection - Subhan, Subhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The purpose of this study was to identify and analyze the influence of professional skepticism, audit experience, and time pressure on fraud detection at the Selayar Islands District Inspectorate. The population in this study were all employees working at the Inspectorate of the Selayar Islands Regency totaling 48 people. The sampling technique for this study used a purposive sampling technique. The data used in this study are primary data collected by distributing questionnaires to all respondents, with data analysis techniques that will be carried out namely validity and reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing consisting of partial tests (t test ) and simultaneous test (test f). The results showed that professional skepticism and audit experience had a positive effect on fraud detection at the Selayar Islands District Inspectorate. Meanwhile, time pressure has a negative effect on the detection of fraud at the Inspectorate of the Selayar Islands Regency.